2010
DOI: 10.1186/1471-244x-10-1
|View full text |Cite
|
Sign up to set email alerts
|

The Autism - Tics, AD/HD and other Comorbidities inventory (A-TAC): further validation of a telephone interview for epidemiological research

Abstract: BackgroundReliable, valid, and easy-to-administer instruments to identify possible caseness and to provide proxies for clinical diagnoses are needed in epidemiological research on child and adolescent mental health.The aim of this study is to provide further validity data for a parent telephone interview focused on Autism - Tics, Attention-deficit/hyperactivity disorder (AD/HD), and other Comorbidities (A-TAC), for which reliability and preliminary validation data have been previously reported.MethodsParents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
354
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 284 publications
(367 citation statements)
references
References 29 publications
10
354
2
Order By: Relevance
“…In previous validation studies, A‐TAC has shown good test–retest measures, excellent inter‐rater reliability, and construct validity 48, 49, 50, as well as convergent validity with the Child Behaviour Check List 51. ADHD traits were calculated as the sum of scores of both the inattention and hyperactivity–impulsivity scales, yielding between 0 and 19 points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous validation studies, A‐TAC has shown good test–retest measures, excellent inter‐rater reliability, and construct validity 48, 49, 50, as well as convergent validity with the Child Behaviour Check List 51. ADHD traits were calculated as the sum of scores of both the inattention and hyperactivity–impulsivity scales, yielding between 0 and 19 points.…”
Section: Methodsmentioning
confidence: 99%
“…ADHD symptoms were divided into three levels of severity: screen‐negative (<6 points), screen‐intermediate (6–7.5 points), and screen‐positive (8 points or more). These cutoffs were based on an earlier validation analysis 49. Response categories were then categorized as 0 (screen‐negative), 1 (screen‐intermediate), and 2 (screen‐positive).…”
Section: Methodsmentioning
confidence: 99%
“…The A-TAC is a tool for screening general populations for child ASD and related conditions, and can also be used as a dimensional measure of ALTs, reflecting the continuous character of the autism spectrum. It has a high sensitivity and specificity (0.96 and 0.88, respectively) for predicting a clinical diagnosis of ASD (Hansson et al, 2005;Larson et al, 2010). The 17 questions on ALTs, 12 of which specifically address the DSM-IV criteria for autistic disorder, reflect the three core symptom dimensions of autism, represented as modules: language impairment (six questions), social interaction impairment (six questions) and restrictive/repetitive behavior (five questions).…”
Section: Measurementsmentioning
confidence: 99%
“…The parents of all twins were contacted when their twins turned 9 or 12 years old, and asked to participate in a telephone interview containing, among other instruments, the Autism-Tics, ADHD and other Co-morbidities inventory (A-TAC) (Hansson et al, 2005;Larson et al, 2010). The A-TAC is a tool for screening general populations for child ASD and related conditions, and can also be used as a dimensional measure of ALTs, reflecting the continuous character of the autism spectrum.…”
Section: Measurementsmentioning
confidence: 99%
“…To end on a positive note: although much can be said about the industry-sponsored follow-up on the consensus statement (Kooij et al, 2010), it does mention both effect sizes from quantitative as well as molecular studies, albeit without highlighting the contrasting findings. And in our data-sample, roughly a quarter of the ADHD sections were classified as “elaborate”, explicating and often contrasting effect sizes of both quantitative and molecular studies.…”
Section: Discussionmentioning
confidence: 99%